2003
DOI: 10.2134/agronj2003.0329
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Oleic Acid Content in Sunflower Oil

Abstract: showed that achenes produced in the cold climates of North America normally contain 70% or more linoleic Knowledge of the effects of temperature and geographic variables acid in oil while those produced in more southern lation the oleic acid content of sunflower (Helianthus annuus L.) oil allows us to predict the type of oil that will be produced in a particular tudes show levels as low as 30%.area. This study was designed to establish a simple empirical model,The genetic modification of sunflower oil fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
4
21
0
Order By: Relevance
“…The mean air temperature tended to be lower and cumulative temperature tended to be higher in F7. Nagao and Yamazaki (1984) and Sobrino et al (2003) reported that the oleic acid to linoleic acid ratio increased with increasing temperature during the grain fi lling stage. In addition, seeds from plants grown at a low temperature had higher activities of microsomal oleoyl phosphatidylcholine desaturase that increase the contents of unsaturated lipids (Garces et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The mean air temperature tended to be lower and cumulative temperature tended to be higher in F7. Nagao and Yamazaki (1984) and Sobrino et al (2003) reported that the oleic acid to linoleic acid ratio increased with increasing temperature during the grain fi lling stage. In addition, seeds from plants grown at a low temperature had higher activities of microsomal oleoyl phosphatidylcholine desaturase that increase the contents of unsaturated lipids (Garces et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This effect of water stress on the content of oil oleic and linoleic acid may be attributed to the activity of the enzyme ⌬12 desaturase (Baldini et al 2000). Baldini et al (2000) found that the increase in oleic acid was due to the activity of ⌬12 desaturase, responsible for the conversion of oleic to linoleic acid, which was affected due to water stress (Baldini et al 2000;Sobrino et al 2003). Furthermore, the author reported that this enzyme acts only for a very short period during the early development of the embryo in water stressed plants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the author reported that this enzyme acts only for a very short period during the early development of the embryo in water stressed plants. Secondly, while working with sunflowers, Sobrino et al (2003) found a strong inverse relationship between oleic and linoleic acid contents and reported that the enzyme ⌬12 desaturase is responsible for these responses. However, Salera and Baldini (1998) observed no effect of water management on oleic acid content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil containing a high level of oleic acid is preferred in nutritional use, whereas that having higher linoleic acid content is preferred by paint or fuel industry. Standard sunflower cultivars contain high linoleic acid, moderate oleic acid and low linolenic acid (Sabrino et al, 2003). Previously, both oil quality and rate in sunflower have been well documented by several researchers (Nolasco et al, 2004;Burton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%